Nurse Staffing and Workload Drivers in Small Rural Hospitals: An imperative for Evidence - Diane E Twigg; Jennifer H Cramer; Judith D Pugh (Online Journal of Rural Nursing and Health Care, 2016)
Purpose: The aim of this study was to explore staffing issues and the workload drivers influencing nursing activities in designated small rural hospitals of Western Australia. A problem for small rural hospitals is an imbalance between nurse staffing resources and work activity.